Wzory kultury gospodarczej jako przedmiot badania. Kilka uwag po lekturze Stosunków pracy… Janusza Hryniewicza - Rotengruber , Przemysław (Człowiek i Społeczeństwo, 2014)
The patterns of culture is a well known phrase which was used for first time by Ruth Benedict. The successors of this tradition believe that culture – in its essence – is governed by rules of a different kind. Anthropologists, sociologists and representatives of cultural studies, focus attention on patterns of very long duration (long-term historical structures which denote a variety of organized behaviours). One of these researchers is Janusz Hryniewicz. According to Hryniewicz, Polish economic practice is deeply involved in the cultural patterns of a so called manor farm origin. Unfortunately, this statement is inefficiently justified. This assumption is supported by circumstancial evidence (similarities between historical events) instead of the proper structural analysis of historical data. The main purpose of this paper is to scrutinize how patterns of culture (especially patterns of Polish economic culture) arise and which factors determine their stability.